2020
DOI: 10.1093/trstmh/trz135
|View full text |Cite
|
Sign up to set email alerts
|

Serological assays for the diagnosis of Strongyloides stercoralis infection: a systematic review and meta-analysis of diagnostic test accuracy

Abstract: The standard method for the diagnosis of Strongyloides stercoralis, stool examinations, is inconvenient and, therefore, serological methods have been proposed. This study aimed to evaluate the accuracy of serological assays for the diagnosis of strongyloidiasis using a systematic review and meta-analysis model. Four electronic databases were reviewed. We used a random effects model and 95% CIs to determine the overall sensitivity, specificity and diagnostic odds ratio (DOR). Heterogeneity was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 38 publications
0
28
0
Order By: Relevance
“…Strongyloidiasis is a human parasitic infection that is still underdiagnosed and underestimated, resulting in a serious public health problem worldwide. Even though the detection of antibodies cannot be useful for post-treatment monitoring, detection of IgG antibodies by ELISA is preferred for the serodiagnosis of strongyloidiasis due to its high sensitivity, reproducibility and its capacity to work with high number of samples, being a powerful tool for both the clinical diagnosis and seroepidemiological studies (Kalantari et al, 2020). However, ELISA requires classify a result as positive or negative and the most used method to choose a cutoff value is the ROC curve analysis, where the AUC determines the inherent ability of the test to discriminate between the diseased and healthy populations (Eusebi, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Strongyloidiasis is a human parasitic infection that is still underdiagnosed and underestimated, resulting in a serious public health problem worldwide. Even though the detection of antibodies cannot be useful for post-treatment monitoring, detection of IgG antibodies by ELISA is preferred for the serodiagnosis of strongyloidiasis due to its high sensitivity, reproducibility and its capacity to work with high number of samples, being a powerful tool for both the clinical diagnosis and seroepidemiological studies (Kalantari et al, 2020). However, ELISA requires classify a result as positive or negative and the most used method to choose a cutoff value is the ROC curve analysis, where the AUC determines the inherent ability of the test to discriminate between the diseased and healthy populations (Eusebi, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis published by Kalantari et al (2020) about serodiagnostic test accuracy using antigens from different Strongyloides species showed that antigens from S. venezuelensis were more sensitive and specific than antigens from S. stercoralis or S. ratti, and proposed that heterologous antigens from S. venezuelensis are an excellent alternative for the serodiagnosis of human strongyloidiasis. The results of the present study confirm the potential use of these antigens obtained from S. venezuelensis iL3 which showed remarkable AUC values over 0.99, being considered with excellent diagnostic accuracy for the detection of IgG anti-Strongyloides antibodies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…86 Because the sensitivity of this method is not ideal, serological assays and molecular biology techniques (PCR) have been suggested as alternatives or additional tools. 87,88 Treatment is preferably accomplished with ivermectin for 2 days, and a second course can be indicated 1 or 2 weeks later. In patients with severe forms, treatment should be continued until symptoms improve and serial stool samples are negative for 2 weeks.…”
Section: Peculiarities Of the Most Frequent Tropical Infections In Kidney Transplant Patientsmentioning
confidence: 99%
“…The traditional microscopic detection of larvae in faeces has unsatisfactory sensitivity; similarly, molecular detection of S. stercoralis DNA in stools by PCR is still considered inadequate for screening purposes [7]. Higher sensitivity can be achieved using serological methods, although there are some concerns about the specificity, particularly when used in endemic areas, due to possible cross-reactions with other nematodes [8,9].…”
Section: Introductionmentioning
confidence: 99%